Neuroimaging in Children with Cerebral Palsy: A Study Conducted at Tertiary Level Paediatric Hospital of Nepal - Manandhar, Bina Prajapati; Singh, Usha; Khatun, Najala (Journal of Nepal Paediatric Society, 2018)
I Introduction: In Nepal, cerebral palsy (CP) is the common cause of severe motor disability. However, only few descriptive studies related to it have been conducted, but those did not incorporate neuroimaging in CP. Thus, the objective of this study is to identify clinical and radiological profile of children diagnosed with CP at a tertiary level paediatric hospital of Nepal. Material and Methods: This study was carried out at Kanti Children's Hospital and the study utilized data of children diagnosed with CP from September 2015- April 2017. Results: A total of 100 children were diagnosed with CP. Spastic CP was the most common in children (71%), followed by mixed (21%) and dyskinetic (8%). Majority of the children were male (74%), born at term (90%) and delivered at institution (80%). Neuroimaging abnormality was found in 66% of cases which included brain malformation (2%), periventricular white matter abnormalities (23%), cortical or deep grey matter lesions (37%) and miscellaneous (4%). The results of this study also showed significant association between variables such as birth weight and birth asphyxia with type of neuroimaging findings. Conclusion: Neuroimaging is helpful for diagnosis of CP and also useful for parents and physicians to understand children condition. Hence, further studies related to neuroimaging in CP are important to better understand it in detail.